Migration in Africa Shifting Patterns of Mobility from the 19th to the 21st Century - de Haas, Michiel; Frankema, Ewout (Taylor & Francis, 2022)
This book introduces readers to the age of intra-African migration, a period from the mid-19th century onward in which the center of gravity of African migration moved decisively inward. Most books tend to zoom in on Africa's external migration during the earlier intercontinental slave trades and the more recent outmigration to the Global North, but this book argues that migration within the continent has been far more central to the lives of Africans over the course of the last two centuries. The book demonstrates that only by taking a broad historical and continent-wide perspective can we understand the distinctions between the more immediate drivers of migration and deeper patterns of change over time. During the 19th century Africa's external slave trades gradually declined, whilst Africa's expanding commodity export sectors drew in domestic labor. This led to an era of heightened mobility within the region, marked by rapidly rising and vanishing migratory flows, increasingly diversified landscapes of migration systems, and profound long-term shifts in the wider patterns of migration. This era of inward-focused mobility reduced with a resurgence of outmigration after 1960, when Africans became more deliberate in search of extra-continental destinations, with new diaspora communities emerging specifically in the Global North. Broad ranging in its temporal, spatial, and thematic coverage, this book provides students and researchers with the perfect introduction to age of intra-African migration.